2020
DOI: 10.1002/celc.202000319
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the NaOH Concentration on the Hydrogen Electrode Reaction Kinetics of Ni and NiCu Electrodes

Abstract: Nickel is a promising electrocatalyst for hydrogen electrode reactions in alkaline media. Its electrocatalytic activity for hydrogen oxidation and evolution reactions can be enhanced when its surface is partially covered by Ni (hydr)oxides or by associating it with Cu. In this work, the influence of the NaOH concentration on the hydrogen electrode kinetics on various Ni electrodes is investigated. On metallic Ni, the electrocatalytic activity (measured as an exchange current density normalized to the surface a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 62 publications
0
5
0
Order By: Relevance
“…While further (preferably in situ spectroscopic) studies are required to unveil the surface state of Ni electrodes during the HOR and thus unambiguously confirm its influence on the reaction kinetics, it should be emphasized that the model proposed by Oshchepkov et al currently presents the most consistent explanation of the available literature data. [48][49][50][51][52] Armed with this knowledge, Oshchepkov et al have recently reported a partially oxidized Ni-NiOx/XC-72 electrocatalyst prepared by electrodeposition technique, which possesses HOR specific activity at the level of a commercial Pd/C electrocatalyst (Table 1). 137 It has been demonstrated that the conductivity.…”
Section: Hor On Monometallic Ni Electrodesmentioning
confidence: 98%
See 3 more Smart Citations
“…While further (preferably in situ spectroscopic) studies are required to unveil the surface state of Ni electrodes during the HOR and thus unambiguously confirm its influence on the reaction kinetics, it should be emphasized that the model proposed by Oshchepkov et al currently presents the most consistent explanation of the available literature data. [48][49][50][51][52] Armed with this knowledge, Oshchepkov et al have recently reported a partially oxidized Ni-NiOx/XC-72 electrocatalyst prepared by electrodeposition technique, which possesses HOR specific activity at the level of a commercial Pd/C electrocatalyst (Table 1). 137 It has been demonstrated that the conductivity.…”
Section: Hor On Monometallic Ni Electrodesmentioning
confidence: 98%
“…In addition, Oshchepkov et al have recently pointed out to the influence of the surface state of Ni electrodes on their HOR/HER activity in the potential interval -0.2 < E < 0.5 V vs RHE. [48][49][50][51][52] Below the most relevant information regarding electrochemistry of Ni electrodes in alkaline media is briefly summarized.…”
Section: Electrochemical Behavior Of Ni In Alkaline Mediamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, our light microscopy and SEM analyses of the surface of the Ni­(poly) electrode demonstrate that there is no noticeable surface roughening that could be attributed to the ultrasonic treatment (this is unique to the cell employed in this research). Consequently, the smaller size of this anodic CV peak as the duration of ultrasonication increases provides evidence that the Ni­(poly) electrode undergoes gradual partial oxidation, the mechanism of which is discussed below. …”
Section: Resultsmentioning
confidence: 99%